Problem-based learning innovation through realism and culture: Impact on mathematical problem solving and self-efficacy in primary school students - Rahman, Arief Aulia; Mushlihuddin, Rahmat; 'Afifah, Nur; Refugio, Craig N; Zulnaidi, Hutkemri (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: Elementary school students in Aceh Tamiang often struggle with problem-solving which negatively impacts their confidence. To address this issue, a new teaching approach called PBL-Reathnomath was developed, combining problem-based learning with real-world math examples and cultural references.Aim: This study aimed to determine the effectiveness of the PBL-Reathnomath model at improving students' problem-solving skills and self-efficacy.Method: A study was conducted involving randomly selecting participants and dividing them into two groups. One group learned using the new PBL-Reathnomath model while the other group learned using traditional methods. Data were collected through tests and surveys and the results were analyzed using statistical methods.Results: The findings showed that the PBL-Reathnomath model significantly improved both the problem-solving abilities and self-efficacy of the students. The group that used this new model performed better on average than the group that used traditional methods. Further analysis confirmed that the PBL-Reathnomath model simultaneously affected problem-solving and self-efficacy, explaining a substantial portion of the variation in these outcomes.Conclusion: While the effect size was smaller compared to conventional learning, the study concluded that PBL-Reathnomath is a valuable and specialized approach for improving problem-solving skills and boosting self-confidence among elementary school students.